1990
DOI: 10.1044/jshd.5502.360
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of Fundamental Frequency and Perturbation in Repeated Phonations of Sustained Vowels, Reading, and Connected Speech

Abstract: The purpose of this study was to determine consistency of the acoustic measurement of fundamental frequency (f0) and f0 perturbation using the Visi-Pitch. Samples of speech including a reading passage, vowels, and spontaneous speech were recorded for 12 normal young adults (6 men and 6 women). The results indicated that test-retest reliability was highest for the reading passage. The measurements of fundamental frequency for reading and spontaneous speech were very similar, but vowel production was, on average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
2

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 9 publications
3
37
2
Order By: Relevance
“…The results of this study indicated that laryngeal function may be different during continuous speaking than during a sustained vowel. Results of previous research on acoustic differences (Brown Jr. et al, 1996;Fitch, 1990;Nittrouer et al, 1990) and differences in supraglottic activity (Stager et al, 2000) that are evidenced across speaking tasks support the task differences seen in this study.…”
Section: Study Strengthssupporting
confidence: 78%
See 1 more Smart Citation
“…The results of this study indicated that laryngeal function may be different during continuous speaking than during a sustained vowel. Results of previous research on acoustic differences (Brown Jr. et al, 1996;Fitch, 1990;Nittrouer et al, 1990) and differences in supraglottic activity (Stager et al, 2000) that are evidenced across speaking tasks support the task differences seen in this study.…”
Section: Study Strengthssupporting
confidence: 78%
“…Incidence of supraglottic activity varies across speaking tasks, and is lower during a sustained /i/ vowel than during several continuous speaking contexts (Stager et al, 2000). Several acoustic characteristics such as fundamental frequency and voice intensity are affected by speaking context, and often differ for sustained vowels as compared to continuous speech (Brown Jr., Morris, & Murry, 1996;Fitch, 1990;Nittrouer, McGowan, Milenkovic, & Beehler, 1990). The task differences in this study suggest that in addition to acoustic parameters and supraglottic activity, patterns of vocal fold vibration may differ for sustained vowels versus continuous speech.…”
Section: Differences In Laryngeal Function Across Tasksmentioning
confidence: 99%
“…Analysing adult voices, Södersten & Hammarberg (1989) found that most perceptual parameters were more prominent in connected speech as compared to sustained vowels. Furthermore, with regard to test-retest reliability, reading a text has been found to yeild more stable data than both running speech and sustained vowel phonation (Fitch, 1990). Sederholm (1996) recently carried out a perceptual study of the same 50 voices as were analysed in the present investigation.…”
Section: Fig 5 Rank Ordered Ascending Mean Values For the Four Acoumentioning
confidence: 99%
“…Data from the National Center for Voice and Speech in the USA are shown in Figure 2.8. There have been a few studies on SFF in singers (Nadoleczny, 1923;Koufman & Blalock, 1988;Brown Jr, et al, 1991;Brown Jr, et al, 1993;Drew & Sapir, 1995;Morris, et al, 1995;Larsson & Hertegård, 2008) (Snidecor, 1951;Mysak, 1959;Schultz-Coulon, 1975;Horii, 1982;Hudson & Holbrook, 1982;Ramig & Ringel, 1983;Fitch, 1990;Traunmuller & Eriksson, 1994;Schiwitz, 2011).…”
Section: Speaking Fundamental Frequencymentioning
confidence: 99%
“…There are many influences on SFF including subject selection criteria and subject variables ( & Hollien, 1963;Honjo & Isshiki 1980;Stoicheff, 1981;Alarcos et al, 1983;Mueller et al, 1984;Linville & Fisher, 1985;Linville, 1987;Pegoraro-Krook, 1988;Higgins & Saxman, 1991;Russell et al, 1995) professional training (McGlone, 1977;Watson & Hixon, 1985;Morris & Brown Jr, 1987;Brown Jr et al, 1988;Brown Jr et al, 1991;Brown Jr et al, 1993;Baken & Orlikoff, 2000;Brown Jr et al, 2000) task type (Mysak, 1959;Horii, 1975;Hudson & Holbrook, 1982;Ramig & Ringel, 1983;Britto & Doyle, 1990;Fitch, 1990;Murry et al, 1995;Zraick et al, 2000;Baker et al, 2008;Schiwitz, 2011) measuring method (Hirano, 1989;Morris & Brown Jr, 1996;Behrman, 2005) anthropometric indices (Bricker & Pruzansky, 1976;Lass & Davis, 1976;Lass et al, 1977;Lass, Barry, et al, 1979;Lass, DiCola, et al, 1979;Lass & Colt, 1980;Graddol & Swann, 1983;…”
Section: Speaking Fundamental Frequencymentioning
confidence: 99%